Leadership in Action: New Model: A Social Entrepreneur Changes the Landscape - Rego, Lyndon; Bhandary, Aparna (Center for Creative Leadership, 2006)
A cardiac surgeon has pioneered a series of innovative solutions that have put health care within the reach of millions of people in India by harnessing state-of-the-art technology, top-flight talent, partnerships, and most of all creative leadership.